2020
DOI: 10.14203/bkr.v23i1.5
|View full text |Cite
|
Sign up to set email alerts
|

KEANEKARAGAMAN RAMBAI (Baccaurea motleyana (Müll.Arg.) Müll.Arg.) DI PULAU BENGKALIS BERDASARKAN KARAKTER MORFOLOGI

Abstract: Bengkalis Island is one of the islands in Riau Province which produced most rambai (Baccaurea motleyana Müll.Arg.) in the province where the plant has been used as fruit and medicinal plants. None of research has been conducted on the diversity of rambai from Bengkalis Island. The purpose of this study was to identify the diversity of B. motleyana in Bengkalis Island based on morphological characters. Exploration method was used in two sub-districts namely Bantan and Bengkalis. Observation included 37 morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Salah satu tumbuhan yang memiliki khasiat sebagai kandidat obat diabetes adalah kulit buah rambai . Indonesia memiliki keanekaragaman hayati tumbuhan khususnya tumbuhan rambai (Ramayani & Fitmawati, 2020).…”
Section: Pendahuluanunclassified
“…Salah satu tumbuhan yang memiliki khasiat sebagai kandidat obat diabetes adalah kulit buah rambai . Indonesia memiliki keanekaragaman hayati tumbuhan khususnya tumbuhan rambai (Ramayani & Fitmawati, 2020).…”
Section: Pendahuluanunclassified
“…This plant serves as a medicinal plant, with applications in treating eye and skin inflammation. Additionally, rambai’s ecological significance extends to being a food source for various animals, including birds, rodents, deer, monkeys, and orangutans ( Ramayani, 2020 ). Evidence showed that B. motleyana exhibits diverse medicinal uses across various cultures.…”
Section: Introductionmentioning
confidence: 99%
“…Durian is a tropical fruit that has unique flavor and aroma. Durian is also called the king of fruit which is very popular among other fruits because of its distinctive taste (Lestari et al, 2011).…”
Section: Introductionmentioning
confidence: 99%